2011
DOI: 10.1007/s11357-011-9310-9
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent modulation of sensory reweighting for controlling posture in a dynamic virtual environment

Abstract: Older adults require more time to reweight sensory information for maintaining balance that could potentially lead to increased incidence of falling in rapidly changing or cognitively demanding environments. In this study, we manipulated the visual surround information during a collision avoidance task in order to investigate how young and elderly adults engage in sensory reweighting under conditions of visual anticipation. Sixteen healthy elderly (age: 71.5±4.9 years; height: 159.3±6.6 cm; mass: 73.3±3.3 kg) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 34 publications
6
36
0
Order By: Relevance
“…It is also questionable whether elderly could conquer this challenge if they were used to performing postural task with eyes shut during their youth. The found differences between condition 'a' and 'c' are in agreement with the findings reported by Teasdale [7] and Eikma [15].…”
Section: Discussionsupporting
confidence: 92%
“…It is also questionable whether elderly could conquer this challenge if they were used to performing postural task with eyes shut during their youth. The found differences between condition 'a' and 'c' are in agreement with the findings reported by Teasdale [7] and Eikma [15].…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, the age-related reorganisation of motor units (Erim et al 1999) and increasing muscular noise (Enoka et al 2003) may alter the ability of the central nervous system to finely mimic the direct relationship between motor commands and their consequences. Finally, as sensory reweighting has shown to be altered with ageing (Eikema et al 2012;Speers et al 2002), it could be extrapolated that reweighting of responsibilities between the pairs of internal models would also be altered in adult ageing. Such an alteration could partly explain the observed shift from a continuous mode of control in young adults toward an intermittent one in older adults.…”
Section: Models Of Control and Internal Modelsmentioning
confidence: 99%
“…Removing visual information on target location upon movement initiation (Elliott et al 1991;Seidler-Dobrin and Stelmach 1998) would solve this problem but produce other limitations associated with the quick degradation of visual information related to the movement environment after visual occlusion (Elliott 1988;Elliott and Madalena 1987). This removal also implies sensory reweighting processes which have shown to be altered in adult ageing (Eikema et al 2012;Speers et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, visual field-dependent individuals are more sensitive to peripheral visual information, such as motion and orientation cues (Amblard et al 1985;Isableu et al 1998;Streepey et al 2007). A shift towards greater visual field dependence has been reported in old adults (Eikema et al 2012;Kobayashi et al 2002;Marendaz 1984;Markus 1971;Panek et al 1978;Poulain et al 2004;Schwatz and Karp 1967;Slaboda et al 2011). However, the determinants leading to this age-related shift in frame of reference selection have not been well defined.…”
Section: Introductionmentioning
confidence: 98%
“…Motor control in itself is more attentionally demanding with age, requiring additional cognitive resources (Seidler et al 2010). Studies have shown that greater visual field dependence in old adults is associated with postural equilibrium alterations, increasing risk of fall (Eikema et al 2012;Jamet et al 2004;Lord and Webster 1990) and leads to more difficulty to perform dual tasks (Maylor and Wing 1996). Moreover, the implication of adaptation and sensory re-weighting difficulties for old adults (Bugnariu and Fung 2007;Eikema et al 2012;Eikema et al 2013;Slaboda et al 2011;Slaboda and Keshner 2012) means risk is even greater under sensory perturbation (e.g.…”
Section: Introductionmentioning
confidence: 99%